2018
DOI: 10.29252/jafm.11.05.28600
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Flow Control over an Ahmed Body using DBD Plasma Actuator

Abstract: Ahmed body is a standard configuration of road vehicles and most of the studies of automobile aerodynamics are performed based on it. In this paper, the plasma actuator was used as an active flow control method to control the flow around the rear part of the Ahmed body with the rear slant angle of 25°. Experiments were carried out in a wind tunnel at two different velocities of U=10m/s and U=20m/s using steady and unsteady excitations. The hot-wire anemometer was used to measure the vortex shedding frequency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In particular, many studies focusing on improvement of wing performance by suppressing the flow separation (Sato et al, 2015;Fujii, 2018) have been conducted in the aerospace field. Regarding applications of PA on automobile flow, aerodynamic noise reduction (Miyamoto et al, 2018) and aerodynamic drag reduction (Shadmani et al, 2018;Kanatani et al, 2009;Vernet et al, 2018) have been studied. These studies aimed to reduce the boundary layer separation from the automobile's body, such as at the roof's end or the rounded pillar, similar to suppressing flow separation on a wing.…”
Section: Aerodynamic Drag Reduction Of a Simplified Vehicle Model By mentioning
confidence: 99%
“…In particular, many studies focusing on improvement of wing performance by suppressing the flow separation (Sato et al, 2015;Fujii, 2018) have been conducted in the aerospace field. Regarding applications of PA on automobile flow, aerodynamic noise reduction (Miyamoto et al, 2018) and aerodynamic drag reduction (Shadmani et al, 2018;Kanatani et al, 2009;Vernet et al, 2018) have been studied. These studies aimed to reduce the boundary layer separation from the automobile's body, such as at the roof's end or the rounded pillar, similar to suppressing flow separation on a wing.…”
Section: Aerodynamic Drag Reduction Of a Simplified Vehicle Model By mentioning
confidence: 99%
“…This position was labeled "Position 1" in this paper. Shadmani [27] realized a good control effect by placing the upper electrode of an actuator at the end of the top surface, i.e., "Position 2" in this paper. However, the conditions for the two groups of tests differed, and thus, no effective comparison could be made.…”
Section: Control Effect Under Different Positions Of the Actuatormentioning
confidence: 90%
“…The maximum drag reduction of 8% at a 10 m/s wind speed was achieved when an actuator was arranged on top of the slanted surface. Shadmani [27] used the steady and unsteady excitation of a plasma actuator to reduce the drag of an Ahmed model (rear slant angle of 25 • ) and found that drag reduction was better with the former than with the latter. The Ahmed body [28] is a simplified geometry of automobiles with different tail characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the control effects of linear and serpentine plasma actuators on the rear flow field of the tractor-trailer truck by Roy et al [33], it was found that the former fails to reduce the drag, while the latter has a big change in the drag, and obtained the drag drops by more than 14% and 10% at an inflow velocity of 26.8 and 31.3 m/s. At the same time, some researchers use plasma actuators to control the airflow separation on the rear window of the Ahmed model, so as to achieve the purpose of reducing drag [34][35][36].…”
Section: Introductionmentioning
confidence: 99%